THE INFLUENCE OF RELIGIOSITY ON MENTAL HEALTH AMONG ACADEMICIANS IN PUBLIC HIGHER EDUCATION INSTITUTIONS IN KELANTAN: A PILOT STUDY - Sakarji, Siti Rosnita; Nik Min, Nik Mohd Faris (International Journal of Accounting, Finance and Business, 2024)
This study in general examined the influence of religiosity in improving academicians’ mental health within the context of the Job-Demand Resource (JD-R) Model. The JD-R Model has been extensively utilised to comprehend how job demands and resources affect workers' performance and well-being. Religiosity, often overlooked as a psychological resource, can play a significant role in mitigating the negative effects of job demands and enhancing employee mental health. Religiosity and spirituality have increasingly gained attention as potential contributors to improving employee mental health. This study also examines the literature and research findings that suggest a significant link between religiosity and enhanced mental health outcomes. To promote a comprehensive strategy for improving mental health in the workplace, it is important to respect employees varied religious perspectives and the necessity of inclusive workplace policies that permit employees to express their religiosity in a way that is consistent with their beliefs. Specifically, for the purpose of this pilot research, this study examines the influence of religiosity on mental health among academicians in three public higher education institutions in Kelantan namely Universiti Teknologi MARA (UiTM), Universiti Sains Malaysia (USM) and Universiti Malaysia Kelantan (UMK). Quantitative data were collected using a questionnaire that was distributed to 33 academicians. The results demonstrate that all the measures exhibited a high level of dependability, with coefficients ranging from 0.872 to 0.977, as determined by the Cronbach's alpha coefficient test. It is worth noting that all these coefficients surpassed the benchmark of 0.70.